2019
DOI: 10.1080/0284186x.2019.1675906
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, clinical and lifestyle-related correlates of accelerometer assessed physical activity and fitness in newly diagnosed patients with head and neck cancer

Abstract: Introduction: Objective measurements of levels of physical activity and fitness in patients with head and neck cancer (HNC) are lacking. Furthermore, demographic, clinical and lifestyle-related correlates of low levels of physical activity and fitness in patients with HNC are unknown. This study aims to investigate the levels of accelerometer that assessed physical activity and fitness in patients with HNC and to identify their demographical, clinical and lifestyle-related correlates. Methods: Two hundred and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 49 publications
2
39
1
Order By: Relevance
“…In conclusion, the available clinical and biological evidence would lead us to conclude that promotion of an active lifestyle, characterized by performance of moderateintensity PA (e.g., between 3 and 6 MET, equaling short distance running) may be beneficial for lowering the risk of developing laryngeal cancer as well as for improving the quality of life of cancer survivors. This specific training regimen seems to be even more effective than high-intensity exercise in individuals at a particularly higher risk of this type of malignancy (49).…”
Section: Discussionmentioning
confidence: 91%
“…In conclusion, the available clinical and biological evidence would lead us to conclude that promotion of an active lifestyle, characterized by performance of moderateintensity PA (e.g., between 3 and 6 MET, equaling short distance running) may be beneficial for lowering the risk of developing laryngeal cancer as well as for improving the quality of life of cancer survivors. This specific training regimen seems to be even more effective than high-intensity exercise in individuals at a particularly higher risk of this type of malignancy (49).…”
Section: Discussionmentioning
confidence: 91%
“…There are only a few studies that have assessed PA prior to oncological treatment and they have reported low level of PA 7‐9 . In addition, lower PA was associated with lower functional wellbeing, higher fatigue, more comorbidity, and higher tumor stage 7,8 . Two of the studies used self‐report methods, 8,9 which are prone to reporting bias.…”
Section: Introductionmentioning
confidence: 99%
“…16 Pre-treatment physical activity levels and physical fitness are typically low, particularly in females, older individuals, and those with lower educational levels. 17 Moreover, physical activity levels have been shown to be substantially reduced post-diagnosis and associated with low levels of physical fitness and functioning. [18][19] Due to the cluster of lifestyle choices associated with poor health outcomes that are frequently observed in HANC survivor cohorts, comorbidities are common 20 and are associated with further reductions in physical activity levels.…”
Section: Characteristicsmentioning
confidence: 99%
“…[18][19] Due to the cluster of lifestyle choices associated with poor health outcomes that are frequently observed in HANC survivor cohorts, comorbidities are common 20 and are associated with further reductions in physical activity levels. 17…”
Section: Characteristicsmentioning
confidence: 99%